2017
DOI: 10.1007/s10562-017-2114-5
|View full text |Cite
|
Sign up to set email alerts
|

Can Ultrasound or pH Influence Pd Distribution on the Surface of HAP to Improve Its Catalytic Properties in the Dry Reforming of Methane?

Abstract: samples were evaluated for their catalytic activity towards dry reforming of methane (DRM) and the reaction was monitored via a thermal conductivity detector, coupled with gas chromatography (GC-TCD). It was found that ultrasound-assisted IE significantly accelerated the process from 3 days to 3 h and with the Pd 0 metal remaining highly distributed upon the HAP with minor changes in catalytic conversions. Moreover, the ultrasound-assisted IW method successfully improved the Pd 0 distribution and catalytic per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 50 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…The second type plays a significant role in the properties of the hydroxyapatite that has a diameter of around 3.5 Å and is delimited by oxygen, Ca 2+ , and P 5+ ions, denoted as Ca 2+ [II] . The calcium ions can be partly replaced by other divalent cations, such as Mg, Fe, Co, Ni, and Pt. , In recent years, Ni/HAP catalysts have also been widely investigated for the DRM reaction. Boukha and his colleagues prepared Ni/HAP catalysts with Ca/P = 1.57, 1.62, 1.67, and 1.73 for DRM reaction, and the results showed that their performance follows this trend: Ca/P = 1.62 > Ca/P = 1.57 > Ca/P = 1.67 > Ca Ca/P = 1.73.…”
Section: Introductionmentioning
confidence: 99%
“…The second type plays a significant role in the properties of the hydroxyapatite that has a diameter of around 3.5 Å and is delimited by oxygen, Ca 2+ , and P 5+ ions, denoted as Ca 2+ [II] . The calcium ions can be partly replaced by other divalent cations, such as Mg, Fe, Co, Ni, and Pt. , In recent years, Ni/HAP catalysts have also been widely investigated for the DRM reaction. Boukha and his colleagues prepared Ni/HAP catalysts with Ca/P = 1.57, 1.62, 1.67, and 1.73 for DRM reaction, and the results showed that their performance follows this trend: Ca/P = 1.62 > Ca/P = 1.57 > Ca/P = 1.67 > Ca Ca/P = 1.73.…”
Section: Introductionmentioning
confidence: 99%